Minat, motivasi dan kemahiran mengajar guru pelatih - Halimah Harun, (penerbit ukm, 2006)
Attitude, interest and motivation play an important role in student achievement. Therefore, teachers as well students should developed their attitude, interest and motivation in the teaching and learning process to achieve the target objectives. This paper discussed on business student teachers’ attitude, interest and motivation and their performance in teaching practice. The study showed that student teachers’ who have positive attitude, highly interested and motivated in teaching, performed better in teaching practice compared to that those who have negative attitude, low interet and motivation in teaching profession.